Altered methylation in tandem repeat element and elemental component levels in inhalable air particles. (23rd November 2013) - Hou, Lifang; Zhang, Xiao; Zheng, Yinan; Wang, Sheng; Dou, Chang; Guo, Liqiong; Byun, Hyang‐Min; Motta, Valeria; McCracken, John; Díaz, Anaité; Kang, Choong‐Min; Koutrakis, Petros; et al.
<x xml:space="preserve">Abstract</x> Exposure to particulate matter (PM) has been associated with lung cancer risk in epidemiology investigations. Elemental components of PM have been suggested to have critical roles in PM toxicity, but the molecular mechanisms underlying their association with cancer risks remain poorly understood. DNA methylation has emerged as a promising biomarker for environmental‐related diseases, including lung cancer. In this study, we evaluated the effects of PM elemental components on methylation of three tandem repeats in a highly exposed population in Beijing, China. The Beijing Truck Driver Air Pollution Study was conducted shortly before the 2008 Beijing Olympic Games (June 15‐July 27, 2008) and included 60 truck drivers and 60 office workers. On two days separated by 1–2 weeks, we measured blood DNA methylation of SATα, NBL2, D4Z4, and personal exposure to eight elemental components in PM2.5, including aluminum (Al), silicon (Si), sulfur (S), potassium (K), calcium (Ca) titanium (Ti), iron (Fe), and zinc (Zn). We estimated the associations of individual elemental component with each tandem‐repeat methylation in generalized estimating equations (GEE) models adjusted for PM2.5 mass and other covariates. Out of the eight examined elements, NBL2 methylation was positively associated with concentrations of Si [0.121, 95% confidence interval (CI): 0.030; 0.212, False Discovery Rate (FDR) = 0.047] and Ca (0.065, 95%CI: 0.014; 0.115, FDR = 0.047) in truck drivers. In office workers, SATα methylation was positively associated with concentrations of S (0.115, 95% CI: 0.034; 0.196, FDR = 0.042). PM‐associated differences in blood tandem‐repeat methylation may help detect biological effects of the exposure and identify individuals who may eventually experience higher lung cancer risk. Environ. Mol. Mutagen. 55:256–265, 2014. © 2013 Wiley Periodicals, Inc.